STRATEGI PENENTUAN HARGA JUAL PERSPEKTIF HUKUM EKONOMI SYARI’AH (STUDI KASUS DI PASAR KAWASAN WISATA RELIGI MAKAM GUS DUR TEBUIRENG JOMBANG) - Pranoto, Singgih; Afif, Abdullah (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2026)
This study aims to analyze the selling price determination carried out by traders in the Gus Dur Tebuireng Tomb religious tourism market, namely the pilgrimage complex of national figure Abdurrahman Wahid, from the perspective of Islamic economic law. This study uses an empirical juridical approach with a field research type, where data is obtained through observation, interviews, and documentation of traders who sell various types of goods such as accessories, clothing, souvenirs, and ready-to-eat food. The results show that traders set prices based on capital costs, operational costs, market conditions, and consumer purchasing power, by implementing strategies such as bargaining, discounts, and selective stock management to maintain product quality and business continuity. From the perspective of Islamic economic law, this pricing practice is in accordance with the principles of justice, honesty, transparency, and willingness between sellers and buyers, because prices are set fairly, do not contain elements of fraud, and are carried out based on mutual agreement, thus reflecting a balance between the goals of gaining profit and maintaining welfare in economic activities.